ГИПЕРТРОФИЧЕСКАЯ КАРДИОМИОПАТИЯ И СОЧЕТАННАЯ КАРДИОЛОГИЧЕСКАЯ ПАТОЛОГИЯ : ОСОБЕННОСТИ ДИАГНОСТИКИ И ЛЕЧЕНИЯ - С. С. Якушин; Е. В. Филиппов (Архивъ внутренней медицины)
Article is devoted to the diagnosis and treatment of hypertrophic cardiomyopathy in conjunction with the most common cardiac disease (ishemic heart disease, chronic heart failure, hypertension). Shown that the combination of hypertrophic cardiomyopathy with cardiac pathology other may worsen the prognosis for these patients.